Evaluation of silver nanoparticles for the prevention of SARS-CoV-2 infection in health workers: In vitro and in vivo; PLoS One; Vol. 16, iss. 8 - Almanza H. Horacio; Moreno S. Sandra; Plascencia-Lopez I. Ismael; Alvarado-Vera M. Martha; Patron-Romero L. Leslie; Borrego B. Belen; Reyes-Escamilla A. Alberto; Valencia-Manzo D. Daniel; Brun A. Alejandro; Pestryakov A. N. Aleksey Nikolaevich; Bogdanchikova N. Nina (2021, 2021)
Title screen